A novel cross-layer framework for large scale emergency communications - Huynh, Vu San Ha; Radenkovic, Milena (2017)
This paper explores the problem of improving coverage and capacity of large-scale communication networks in disaster-struck areas. We propose a novel integrated dynamic cross-layer distributed energy aware emergency framework, E3F, that spans large geographical areas and variable time ranges. E3F enables adaptive storage, dynamic packet scheduling and utility driven forwarding that avoids congestion and energy depletion. Our extensive experiments with realistic traces show significantly improved energy efficiency and low overheads while maintaining high success ratios for both data dissemination and query answering.